Законодавча влада в Республіці Польща - Марчук, М. І.; Marchuk, M. I.; Марчук Микола Іванович (Право і безпека. – 2018. – № 4 (71). – С. 22-28, 2018)
Розглянуто проблематику дослідження конституційно-правових аспектів функціонування двопалатного парламенту в Республіці Польща. Установлено, що польська конституційна доктрина передбачає асиметричну двопалатну модель парламенту зі збереженням системної еквівалентності палат. Досліджено особливості правового статусу Сейму та Сенату як палат політичного представництва суверенної польської нації. З’ясовано особливості функціонального розмежування повноважень Сейму і Сенату у світлі національного та європейського законодавства.

The article is focused on the problems of studying the constitutional and legal aspects of the functioning of the bicameral parliament in the Republic of Poland. The research is carried out with the aim of studying and scientific understanding of the practical implementation of certain aspects of bicameralism in Ukraine. The peculiarities of the legal status of the Sejm and the Senate as the chambers of political representation of the sovereign Polish nation have been analyzed. It has been emphasized that certain competencies of legislative power in the Polish power system are intended to compensate for the strong positions of the executive branch, due to the assignment of the President of the Republic of Poland to it. It has been noted that in the period after the restoration of the bicameral structure of the Polish Parliament in 1989, until 2010, the Sejm held the dominant position. It has been established that at the present stage of development, the Polish constitutional doctrine foresees an asymmetric bicameral parliament model with the preservation of the system’s equivalence of chambers. It has been noted that the result of the accession of the Republic of Poland to the European Union, the Sejm and the Senate had functional changes that covered almost all the powers of the national parliament, including, first of all, legislative and control functions, led to the appearance of elements of the “European” function of the parliament and transformed already existing commitment of both chambers. The peculiarities of the influence of the EU legal acts on the processes of national legislation in Poland have been revealed. The directions of transformation of the normative and controlling function of the Sejm and the Senate have been determined. The principles of functional separation of powers of the Sejm and the Senate in the light of the national and European legislation have been established. It has been concluded that during the process of implementation of acts of the European law in the national legal system of the Republic of Poland, the chambers of the parliament managed to expand their powers at the expense of the so-called “European competence of the Polish parliament”.

Рассмотрена проблематика исследования конституционно-правовых аспектов функционирования двухпалатного парламента в Республике Польша. Установлено, что польская конституционная доктрина предусматривает асимметричную двухпалатную модель парламента с сохранением системной эквивалентности палат. Исследованы особенности правового статуса Сейма и Сената как палат политического представительства суверенной польской нации. Выяснены особенности функционального разграничения полномочий Сейма и Сената в свете национального и европейского законодательства.
Legislative power in the Republic of Poland
Законодательная власть в Республике Польша
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Польща; Польша; Poland; Республіка Польща; Republic of Poland; Республика Польша; зарубежный опыт; foreign experience; зарубіжний досвід; парламент; бікамералізм; законодавча влада; законотворча діяльність; регламент; представницька функція; бикамерализм; законодательная власть; законотворческая деятельность; регламент; представительская функция; parliament; bicameralism; legislative power; law-making activity; regulation; representative function